CORRELATION BETWEENAUTONOMOUS LEARNING AND ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS: A CASE OF PAKISTAN - Chand Habiba, Dr. Tariq Hussain, Ali Hassan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The current study considered the four constructs of the autonomous learning i.e., learner desire, learner resourcefulness, learner initiative and learner persistence as identifies by (Confessore& Park, 2004) and to examine its relationship with academic performance of the students. Thus, correlation research design was followed in this study. For achieving the study objectives, data was collected from the bachelors and masters level students studying at the discipline of education in public and private sectors universities located in Lahore. A sample of 350 students was chosen in the current study from two public and two private sector universities through convenient sampling technique. The findings of the study revealed that all the four constructs were having significant positive relationship with the academic performance of the students. However, the study revealed that desire construct of the autonomous learning shown significant correlation at level of (p< .01), indicating that there are 99 percent chances that the results are correct, while the value of the correlation coefficient for resourcefulness, initiative and persistence was significant at (p< .05) meaning that there were 95 percent chances that the results are correct. The study recommended that the educational institutions should allow the students and provide them with such environment facilitated with the autonomous learning.